Determinants of participation in child's education and alternative activities in Pakistan - Abdul Salam Lodhi; Daniel Tsegai; Nicolas Gerber (University of Bonn, Center for Development Research (ZEF), 2011)
Using data from Pakistan, this study analyzed the effect of various individual, household, and community level characteristics on the probability that children engage in different activities. According to the existing trend of their prevalence, we considered five child's activities, namely: secular schooling; religious education; child labor; a combination of child labor and secular schooling; and inactivity (including leisure). Data was collected through field surveys conducted in over 40 villages in four Pakistani provinces: Balochistan, Khyber Paktunkhwa, Punjab, and Sind. A total of 963 households were interviewed on the activities of 2,496 children. Multinomial Probit model was used for the analyses. Results indicated that parental perception had significant relationship to the probability of engagement in secular school attendance, religious education, and child labor. In addition, we investigated the relationships between participation in the different child activities with location (rural/urban) and children's gender. We detected a lower probability of attending secular school and a higher probability of engaging in child labor among female children in rural areas. We also found that even parents who openly expressed appreciation of the importance of secular schooling were more likely to send male children to school than female children.
Keywords: 330; Child productivity; child's activities; Parental perception; Gender; Kinder; Schulbesuch; Kinderarbeit; Religion; Eltern; Wahrnehmung; Pakistan